The Nature of Policy-Making in Universities - Taylor, William H. (Canadian Journal of Higher Education, 1983)
Policy-making in universities has been characterized in a variety of ways. The bureaucratic, collegial, political, and organized anarchy models have all been proposed as descriptions of the process. Although each of these models is useful in the study of university policy-making, they fail to provide a complete explanation of the phenomenon. An alternate approach to the conceptualization and analysis of policy-making is proposed and applied to a recent case at The University of Calgary. The proposed model describes policy-making as a set of "policymaking systems" each of which is temporary in nature and develops in response to an identifiable stress in the institutional environment.